Effects of Applied Ratio of Nitrogen on the Light Environment in the Canopy and Growth, Development and Yield of Wheat When Intercropped - Luo, Chaosheng; Guo, Zengpeng; Xiao, Jingxiu; Dong, Kun; Dong, Yan (Frontiers in Plant Science, 2021)
Changes in the light environment have an important effect on crop growth and yield. To clarify the effects of intercropping and the application of nitrogen on the yield of wheat and light within the crop canopy, the relationship between light and yield and their response to nitrogen fertilizer were studied. In a two-year field experiment, the characteristics of growth, light, biomass, and yield of wheat were measured using three cropping patterns (monocropped wheat, monocropped faba beans, and intercropped wheat/faba beans) and four levels of nitrogen application, in groups termed N0 (0 kg/ha), N1 (90 kg/ha), N2 (180 kg/ha) and N3 (270 kg/ha). The results demonstrated that nitrogen fertilizer application increased wheat plant height, spike leaf length and width, and the number of leaves while significantly decreasing wheat canopy light transmittance (LT) and canopy photosynthetic active radiation transmittance (PART), by 7.5 to 71.1% and 12.7 to 75.1%, respectively. There was a significantly increased canopy photosynthetic active radiation interception rate (IPAR) of 7.5 to 97.8% and an increase in biomass of 9.6 to 38.4%, of which IPAR, biomass, and yield were highest in the N2 level. Compared with monocropping, intercropping increased the parameters of wheat growth to varying degrees. Intercropping decreased LT and PART by 10.8 to 46.4% and 15.7 to 58.7%, respectively, but increased IPAR by 0.1 to 66.0%, and wheat biomass and yield by 7.5 to 17.4% and 27.7 to 47.2%, respectively. The mean yield of intercropped wheat increased by 35.8% over two years, while the mean land equivalent ratio (LER) was 1.36, values greater than 1 that indicated the advantageous nature of wheat and faba bean intercropping. Correlation analysis demonstrated that there was a very significant negative correlation between wheat LT and yield, while simultaneously demonstrating a very significant positive correlation between PART and IPAR with yield, indicating that the efficient interception and utilization of light energy in intercropping was the basis for the higher biomass and yield of wheat. In summary, wheat/faba bean intercropping and the application of nitrogen at 180 kg/ha were effective in increasing wheat yield.